Poselska aktywność kobiet na mównicy sejmowej w dobie II RP - Fiktus, Paweł (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
At the moment Poland regained independence after the First World War, women have acquired active and passive suffrage. Already at the time of the first parliamentary activities, they received first deputy mandates. Women sat in pre-war Polish parliament in all its cadences until the outbreak of World War II. Analysing the whole discourse in which they participate, it should be noted that they avoided participation in work on legal solutions which later were included in the Constitution or are the most important acts of rank Codes or relating to the functioning of the vital organs of state. Their legislative activity focused on issues related to education, upbringing, education or social affairs. Another area in which women actively participated refer to matters related to the budget and the ratification of international instruments. Women do not avoid participation in the development of controversial laws which was, for example: amnesty or statute concerning ritual slaughter. The proportion of women in parliament was not dominant. However, it is their voice in the discourse of parliament Second Republic which has signed up as important and interesting. It is worth adding that political activity was continued by women, not only in parliament but also in the Senate
Keywords: Parliament; deputies; women; political life; parliamentary discourse; Poland; 1918-1939